On Legislation and guidelines governing diocesan seminary and ongoing formation. The evolution of the program of Priestly formation in the United States of America - Borgmann, Ernest S. ([Verlag nicht ermittelbar], 2017)
Thesis ad Doctoratum in Iure Canonico. Partim edita